Review of the recent advances on the fabrication, modification and application of electrospun TiO2 and ZnO nanofibers for the treatment of organic pollutants in wastewater - Mapukata, Sivuyisiwe; Shingange, Katekani; Mokhena, Teboho (Frontiers in Chemical Engineering, 2023)
The heightened occurrence of emerging organic pollutants (EOPs) in aquatic bodies has been the subject of global apprehension due to the toxicity they pose to the environment, humans and animals alike. The presence of EOPs has soared due to industrialization and is further exacerbated by human activities like the overuse and poor disposal of dyes, pesticides, pharmaceuticals, surfactants, personal care products and food additives. The complete treatment and removal of EOPs from industrial wastewater and sewage has remained a challenge because of their pseudo-persistence and resistance to degradation. Due to their impressive light absorption properties, high surface-area-to-volume ratio, high porosity, superior mechanical strength, electrospun titanium dioxide (TiO2) and zinc oxide (ZnO) nanofibers have been proposed for photocatalytic treatment of EOPs. Therefore, this review first highlights the fabrication and modification methods of TiO2 and ZnO nanofibers. A systematic survey of the latest progress in the application of TiO2 and ZnO nanofibers for the degradation of EOPs is then elaborated. Thus, the main goal is to shed light and give insight to researchers on the possibilities surrounding the elimination of EOPs by applying electrospun TiO2 and ZnO semiconductor materials.In addition, the loopholes associated with fabrication and modification processes are discussed with the aim of encouraging innovation for prospective technology advancement and commercialization, as well as to enhance research efforts in wastewater treatment and environmental sustainability.